Influence of meteorological variables on the development in plantation of Tachigali vulgaris L.G. Silva & H.C. Lima (tachi-branco) - Ferreira Palheta, Lenilson; Oliveira Simões, Pedro Henrique; Prado Neves, Raphael Lobato; da Silva Ataíde, Wander Luiz; de Paula, Manoel Tavares; Carvalho Dornelas, Karoline; Santiago, Alailson Venceslau; Pereira de Carvalho, João Olegário (Italian Journal of Agrometeorology, 2024)
The objective of this work was to evaluate the influence of meteorological variables on height and diameter increment in a Tachigali vulgaris plantation fertilized with NPK. The meteorological data were recorded by the agroclimatological station of Embrapa Amazônia Oriental, located in Igarapé-Açu, in the period from March 2016 to June 2018. The monitoring of the increment rate in height and diameter of the plants was done. The data collected were: monthly temperature, average maximum temperature, average minimum temperature andprecipitation. The maximum quarterly periodic increment in height occurred in the June-September 2017 quarter, while the highest diameter increment occurred in the June-September 2016 quarter. Principal component analysis showed that the first three factors together explained 94% of the total variance of the species’ growth, where the unfolding analysis of the first two principal components showed that the variables that contributed most to explain the species’ stand development correlated with the climate measures observed in this study, were mean and maximum temperatures and precipitation, followed by height, diameter and minimum temperature. It was concluded that the weather variables positively influenced the increment in height and diameter of plants Tachi, with precipitation being the variable with the greatest contribution to predicting tree growth.